1998
DOI: 10.1074/jbc.273.21.13157
|View full text |Cite
|
Sign up to set email alerts
|

ADP-ribosylation Factor and Rho Proteins Mediate fMLP-dependent Activation of Phospholipase D in Human Neutrophils

Abstract: Activation of intact human neutrophils by fMLP stimulates phospholipase D (PLD) by an unknown signaling pathway. The small GTPase, ADP-ribosylation factor (ARF), and Rho proteins regulate the activity of PLD 1 directly. Cell permeabilization with streptolysin O leads to loss of cytosolic proteins including ARF but not Rho proteins from the human neutrophils. PLD activation by fMLP is refractory in these cytosol-depleted cells. Readdition of myr-ARF1 but not non-myr-ARF1 restores fMLP-stimulated PLD activity. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 61 publications
2
60
1
Order By: Relevance
“…Within 5-10 min a substantial proportion of ARF1 proteins was found in the supernatant. In contrast, Rho proteins did not substantially leak out of cells, similar to results obtain previously with human neutrophils [16].…”
Section: Loss Of Secretory Function and Pld Activation From Permeabilsupporting
confidence: 73%
See 1 more Smart Citation
“…Within 5-10 min a substantial proportion of ARF1 proteins was found in the supernatant. In contrast, Rho proteins did not substantially leak out of cells, similar to results obtain previously with human neutrophils [16].…”
Section: Loss Of Secretory Function and Pld Activation From Permeabilsupporting
confidence: 73%
“…Two mammalian PLD enzymes (PLD1 and PLD2) have been cloned [13,14]. Regulation of PLD1 has been intensively studied and is known to be directly and synergistically regulated by ARF1, Rho proteins (RhoA, Rac and Cdc42) and protein kinase Cα [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…1), and in agreement with previous observations (16). Pretreatment with 100 ng/ml pertussis toxin (22) did not reduce MP release from fMLP-or IL-8-stimulated PMN suspensions (Fig. 1).…”
Section: Inflammatory Stimulation Of Pmn Induces Membrane Mpmentioning
confidence: 99%
“…We have previously demonstrated that ARF translocation correlated with fMLP-induced PLD activation in HL60 granulocytes [15]. More recently, a concomitant PLD activation and rapid enrichment of RhoA in the particulate fraction was documented in LPAstimulated Rat1 fibroblasts [29] and fMLP-stimulated neutrophils [16]. Despite these advances, many aspects of the mechanisms linking receptor occupation to PLD activation remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that ARF translocated to the membrane fraction of HL60 cells in response to fMLP and that this translocation correlated with an increase in the GTP␥S-stimulated membranebound PLD activity [15]. Phorbol 12-myristate 13-acetate (PMA), a non-physiological PKC agonist, had a similar effect on membrane-bound PLD activity and ARF translocation [15].fMLP in neutrophils [16] and that lysophosphatidic acid (LPA) stimulation induces the enrichment of RhoA in the particulate fraction of Rat1 fibroblasts [17].…”
Section: Introductionmentioning
confidence: 94%